Para instruir o espírito e melhorar o coração": compêndios escolares de filosofia racional e moral em Sergipe no século XIX - Santos, Marcus Éverson (2013)
During the nineteenth century secondary schools in Sergipe received an influx of a cultural object important to the school culture of the time: the textbooks and book scholar. These textbooks were intended to meet the requirement of the regulations and decrees teaching in various school subjects among which the Rational and Moral Philosophy. By their methods and content textbooks aimed at improving morally and rationally instruct the hearts of the students. Thus, the general objective and specific this study was to analyze the contents for teaching these subjects in secondary school; show how the disciplines were organized Rational and Moral Philosophy; highlight the presence of textbooks Rational and Moral Philosophy of which contributed to the school culture Sergipe. The main hypothesis of the study was to show that the understanding of philosophy that had in the nineteenth century as "science", "doctrine" or "discipline" allowed the organization of content required for their teaching and, in turn, the textbooks were teaching tools favored for achieving this. The contents of textbooks Rational and Moral Philosophy congregated a set of theoretical knowledge, practical and propaedeutic that shaped secondary education and contributed to the formation of a school culture in the provinces Sergipe.